Las democracias en America Latina: un balance con consecuencias políticas - Morlino, Leonardo (SocietàMutamentoPolitica, 2018)
This paper starts from the application to Latin America of an analytical tool that has been developed to evaluate the quality of democracies and is based on the three notions of quality, in terms procedures (rule of law, electoral accountability, inter-institutional accountability, participation and political competition), content (freedom and socio-economic equality), and result (responsiveness). It takes in full consideration the previous research of the author on the area, and underlines both the major shortcomings that the empirical work has brought out and the most appropriate policies that should be implemented in order to improve the democratic quality of those countries. Obviously, the absence, partial or complete, of the actual conditions to put in place those policies is another matter and depends on other and related factors that would require subsequent empirical research to be enucleated.